Moral and Political Crisis of Intersubjectivity in Europe and Ukraine: Implementation of Deliberative Democracy Idea - Luchak, Mykola; Luchak-Fokshei, Anna-Maria (My University, 2020)
The article explores formation of new ideals and values that has become a key task of the European community after overcoming totalitarianism. Many researchers of that time were looking for methods to prevent atomization and establish democracy, and one of the methods was communicative philosophy. This approach helped to shape the main narratives that still shape the politics of Western Europe. However, Brexit, the international economic crisis of 2008-2011, the COVID-19 pandemic are Black Swans that each time set the tone for the mood of society and determine the meanings of narratives on social networks (virtual and real). The communicative-network transformation of society is capable of materializing the discourse around new problems of the world in order to prevent a moral split. The virtual dimension of our everyday life acquires key roles in the dissemination of thoughts and shaping the mood of society. This transformation creates new threats to liberal values that were formed long before the “state in the smartphone”. Focusing attention on the modern conditions of human life will help to better understand its political behavior and ways to create better conditions for democracy in modern society.
Keywords: Political Science; Government